Analysis of Financial Business Sustainability Study on Conventional Banks, Islamic Banks and Coop - Danny Wibowo (Budapest International Research and Critics University, 2021)
The sustainability of the financial business at conventional banks, Islamic banks and cooperatives is emphasized on indicators of socio-culture and society, business profits and the natural environment, research is carried out by conducting studies on literacy derived from previous studies and data released by local authorities. The results showed that the potential for business sustainability of conventional banks in Indonesia is still very good as evidenced by the high profit, the potential for saving people is still very large and the increase in assets and credit distribution, even though Islamic banks are affected by the pandemic, the contraction is very small, besides that Islamic banks are also very low. Good efficiency as well as a very large potential for the Islamic market or around 90% of the total population of Indonesia. Meanwhile, cooperatives in terms of profitability are not good enough, the dominance of millennials and generations who are less interested in cooperatives is an obstacle to the development of cooperatives.